'I don't want orange trees, I want something that others don't have': Ottoman Head-Gardeners after Mahmud II. (1st October 2015) - Türker, Denİz
Among the many effects of the Tanzimat period's political and cultural reforms was an overhaul of the physical appearance of the house of Osman. Borrowing from their immediate predecessor Selim III, sultans of the nineteenth century hired foreign horticultural experts to design their imperial gardens. The new post of the head-gardener, continually refilled by European expatriates until the early twentieth century, would revitalize the once prominent, pre-Tanzimat court institution of the gardeners' corps. This article provides an in-depth look at the first of these figures, Christian Sester from Bavaria, who would design and install the last and largest of these imperial sites – the groves of Çragan Palace that would later become the Yldz palatial complex – and in the process reconfigure the corps with a group of his disciples. Sester's scholastic foundation in the vibrant European milieu of the German Enlightenment later primed him to become the 'noble' garden expert among the equally multicultural émigré community that he would form in the Ottoman capital.